Older Sarawakian socioeconomic determinants by sex disaggregation and poverty status - Zainalaludin, Zumilah; Saidi, Norehan; Jamaluddin, Askiah (Human Resource Management Academic Research Society, 2022)
This paper aims to identify the socio-economic determinants significantly predict poverty status of older respondents by sex disaggregation. A total of n=172 respondents reported, and four Hos tested through Binary Logistic Regression Model 1-4, respectively. All Hos were rejected because all models fit and significant (p<0.05). Through HO1 and HO2 testing respectively among male respondents, two predictors obtained – working status and district. In Model 1 and 2, working status predicts less than 88.6 percent and 8.784 times likelihood the respondents were in non-poor and poor category respectively. In Model 1, Miri Sibu, and Betong districts had significantly (p<0.05) predict 9.439 times, 51.352-, and 26.402-time likelihood the respondents were in non-poor category. Whereas in Model 2, Miri, Sibu, and Betong districts had significantly (p<0.05) predict less than 89.4 percent, 98.1 percent, and 96.2 percent likelihood the respondents were in poor category, respectively. Through HO3 and HO4 test respectively among female respondents, two predictors were obtained – strata and current transfer. Rural strata predict less than 79.1 percent (Model 3) and 4.789 likelihood (Model 4) the respondents were in non-poor and poor category respectively. Current transfer predicts less than 99.1 percent (Model 3) and 113.44-time (Model 4) likelihood the respondents were in non-poor and poor category respectively.